Undescribed abietane-type diterpenoids and oleanane-type triterpenoids from the stem and branch of Tripterygium wilfordii. (September 2022) - Hu, Ya-Lin; Xu, Tian-Qi; Cheng, Huai-Yu; Liu, Ying; Zhang, Xia; Zhang, Yu-Bo; Zhou, Guang-Xiong
Abstract: Six undescribed abietane-type diterpenoids (tripterydinoids A-F) and five undescribed oleanane-type triterpenoids (tripterytrinoids A-E) were obtained and determined from the stem and branch of Tripterygium wilfordii Hook. f. (Celastraceae). Tripterydinoids A-C possessed the abietane-type diterpenoid skeleton with rare 8, 9-epoxy ring. The structures of undescribed compounds were established by extensive spectroscopic studies [HRESIMS, 1D/2D-NMR and electronic circular dichroism (ECD) calculation]. The absolute configurations of tripterydinoids A, B, E and tripterytrinoid A were defined by X-ray crystallographic analyses. Bioactivity screening indicated that tripterydinoids A-C exhibited potent inhibitory effects against NO release in LPS-activated RAW 264.7 macrophages with IC50 values of 6.93, 4.46 and 2.98  μ M, respectively. Meanwhile, tripterydinoids A-D and tripterytrinoids B, C showed moderate and selective cytotoxicities against five human tumor cell lines (A375, Huh7, MCF-7, HCT-116 and NCI–H460). Graphical abstract: Six undescribed abietane-type diterpenoids and five undescribed oleanane-type triterpenoids were isolated from the stem and branch of Tripterygium wilfordii Hook. f. Their cytotoxic activity and inhibitory effect against NO release were evaluated. Image 1 Highlights: Eleven undescribed terpenoids were isolated from Tripterygium wilfordii Hook. f. Structures were elucidated by HR-MS, NMR, ECD and X-ray crystallographic analyses. Some compounds exhibited cytotoxicity and inhibitory effect against NO release.